Visit-to-visit lipid variability on long-term major adverse cardiovascular events: a prospective multicentre cohort from the CORE-Thailand registry - Chutithep Teekaput; Kitti Thiankhaw; Wanwarang Wongcharoen; Narawudt Prasertwitayakij; Siriluck Gunaparn; Arintaya Phrommintikul (Scientific Reports)
Abstract Lipid variability (LV) has been studied and proposed as a potential predictor for cardiovascular disease (CVD), and increased LV may contribute to adverse clinical outcomes. This study aimed to investigate the association of various LV parameters with the risk of long-term major adverse cardiovascular events (MACE) among the Thai population. The study used data from the CORE-Thailand Registry, a prospective multicentre study of adults with high cardiovascular risk or established CVD. The primary outcome was 4-point MACE, including non-fatal myocardial infarction, non-fatal stroke, heart failure hospitalisation, and all-cause mortality. LV was defined as visit-to-visit variability in individual and combined lipid parameters using the coefficient of variation (CV), and patients were stratified into four groups according to CV quartiles. The hazard ratio (HR) and 95% confidence interval (CI), adjusted for potential confounders, were calculated using the Cox proportional hazards model. In a total of 9,390 patients, 6,041 patients with data of intra-individual LV were included. After adjusting covariates in the Cox proportional hazards model, higher LV was independently associated with an increased risk of 4-point MACE (HR for quartiles 2, 3, and 4 of the CV of total cholesterol, compared to first quartile, were 3.63 (95% CI 3.20–4.06, P < 0.001), 6.85 (95% CI 6.23–7.47, P < 0.001), and 8.91 (95% CI 8.18–9.64, P < 0.001), respectively). The present study demonstrated that higher visit-to-visit LV, particularly in the higher quartiles, was independently associated with MACE, MI, and all-cause mortality in the Thai population at high cardiovascular risk or established atherosclerotic CVD, indicating that LV might be useful as a potential risk indicator.